Respuesta :

Answer:

  2. Check your work

  3. Correct

Step-by-step explanation:

2. The equation tells you ...

  [tex]a_2=2a_1+4=2(-1)+4=-2+4=2[/tex]

Only one answer choice has +2 as the second term of the sequence. The one you selected is not it.

__

3. The expression can be simplified to ...

  [tex]a_n=\dfrac{(n+3)!}{n+3}=(n+2)![/tex]

Filling in n=1 tells you all you need to know:

  [tex]a_1=(1+2)!=3\cdot 2\cdot 1=6[/tex]

The answer you selected has a first term of 6, so your choice is correct.

Answer:

Answer:

 2. Check your work

 3. Correct

Step-by-step explanation:

2. The equation tells you ...

 

Only one answer choice has +2 as the second term of the sequence. The one you selected is not it.

__

3. The expression can be simplified to ...

 

Filling in n=1 tells you all you need to know:

 

The answer you selected has a first term of 6, so your choice is correct

Step-by-step explanation: